Social individuation: Extending the scale of emotional development – Short (SED-S) for adolescent reference ages. (September 2022) - Tarasova, D.; Zepperitz, S.; Ronsse, E.; Vonk, J.; Zaal, S.; Hudson, M.; Sappok, T.
Abstract: Background: The SED-S is a standardized diagnostic instrument for assessing emotional development (ED) in people with a disorder of intellectual development. The SED-S defines five ED stages covering emotional reference ages up to 12 years in eight domains (5 items per domain). Stage 6 will extend the scale for early adolescent reference ages. Aims: The aim of this study is to define the SED-S items for stage 6 ('Social Individuation'). Methods and procedures: Experts in developmental psychology phrased 56 items (7 items/domain) describing typical behaviors for emotional reference ages 13th-18th year (145th-216th month) in English, German and Dutch. Twenty-eight independent experts assessed the items' content validity and observability on a Likert scale (0 = good to 3 = unacceptable ). Two items/domain with the lowest ratings were excluded to finally select 5 items/domain for SED-S stage 6. Outcomes and results: The ratings were good with results ranging from 0.06 to 0.78 for validity and 0.06–1.78 for observability. After exclusion of the 2 lowest ranking items/domain, a set of 40 items was selected. Conclusions and implications: The SED-S is extended to allow the assessment of emotional reference ages up to 18 years. Further research should evaluate the scale's psychometric properties. What this paper adds?: The current version of the SED-S covers emotional reference ages up to 12 years (144 months). Extending the SED-S for emotional reference ages up to 18 years (145th-216th months of life) in Dutch, German and English allows better differentiation in the higher ED range and expands the applicability of the scale. Specifically, it makes it possible to apply the SED-S in people with borderline intellectual functioning. Accounting for the level of ED may provide valuable information about the behaviors and needs of individuals with higher reference ages and may support targeted treatment options in a population highly vulnerable to behavioral or mental disorders. Highlights: The SED-S assesses emotional development in people with disordersof intellectual development . Our paper extends the SED-S for stage 6 ("Social Individuation") and defines the items to cover adolescent reference ages. We formulated 40 additional items (five in eight domains) for stage 6 of the SED-S. The items were defined in 3 languages by a European working group, thus increasing the scale's international applicability Extending the SED-S will improve the scale's applicability in people with borderline intellectual functioning.